2021
DOI: 10.3389/fphar.2021.682713
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Lessens Gastric Precancerous Lesions by Interfering With β-Catenin/TCF4 Interaction

Abstract: Background: Seeking novel and effective therapies for gastric precancerous lesions (GPL) is crucial to reducing the incidence of gastric cancer. Ginsenoside Rb1 (GRb1) is a major ginsenoside in ginseng and has been proved to possess multiple bioactivities. However, whether GRb1 could protect against GPL and the underlying mechanisms have not been explored.Methods: We evaluated the effects of GRb1 on gastric precancerous lesions in rats on macroscopic, microscopic and ultramicroscopic levels. Then, an antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Rb1 is a kind of dammarane triterpenoid saponin, which is considered to be one of the most important active components in ginseng and a primary component playing a pharmacological role. Rb1 has many bene cial effects on the human body, including cardiovascular and central nervous system activities, anti-diabetic, and anti-tumor activities (27)(28)(29)(30). Rb1 can reduce oxidative stress, inhibit in ammation, downregulate MDA, inhibit ROS, and promote GSH expression, due to its bene cial characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Rb1 is a kind of dammarane triterpenoid saponin, which is considered to be one of the most important active components in ginseng and a primary component playing a pharmacological role. Rb1 has many bene cial effects on the human body, including cardiovascular and central nervous system activities, anti-diabetic, and anti-tumor activities (27)(28)(29)(30). Rb1 can reduce oxidative stress, inhibit in ammation, downregulate MDA, inhibit ROS, and promote GSH expression, due to its bene cial characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used for the management of GPL in clinical practice. Zeng et al [ 33 ] found that Weipixiao can inhibit cell proliferation and induce apoptosis by inhibiting abnormal activation of the Wnt/β-catenin signaling pathway, while GRb1 can inhibit β-catenin protein expression. Downstream targets, such as c-myc, Cyclin D1, Lgr5, MMP-7, and Birc5, in this pathway are inhibited.…”
Section: Mechanism Of Tcm In the Treatment Of Gplmentioning
confidence: 99%
“…For example, WFC can increase the secretion of pepsin by inhibiting the MAPK signaling pathway, thereby regulating the weight of rats with GPL and improving histopathological changes in the gastric mucosa[ 32 ]. Another study showed that Ginsenoside Rb1 (GRb1), which is contained in WFC, can prevent the occurrence and progression of GPLs by reducing the protein expression and nuclear translocation of β-catenin, interfering with the interaction of β-catenin/TCF4, and inhibiting the transcriptional activity of downstream genes, including c-myc, Cyclin D1 and Birc5[ 33 ]. Therefore, it is important to study the effect of TCM on GPL to improve the clinical efficacy and transformation of drug research and development (R&D).…”
Section: Introductionmentioning
confidence: 99%
“…β-linked protein upregulation and nuclear translocation are significantly associated with advanced gastric precancerous lesions (GPL). Zeng et al ( Zeng et al, 2021 ) observed that GRb1 reduced the protein expression and nuclear translocation of β-catenin, interfered with β-catenin/TCF4 interactions, and prevented the development and progression of GPL.…”
Section: Prevention Of Precancerous Lesions By the Active Ingredients...mentioning
confidence: 99%